Revealing the Philosophical Foundation in English Textbook for Vocational School Students Grade X and Curriculum 2013 - Fatma Rahayu Nita; Oikurema Purwati (VELES Voices of English Language Education Society, 2021)
Both philosophy and curriculum are a crucial part of education. Philosophy becomes a very important foundation of the curriculum since it affects the objectives of learning and content, as well as the structure of the curriculum (Ornstein & Hunkins, 2018). Thus, philosophy is included in the three aspects of curriculum development. It also aims to determine the process of teaching and learning. Therefore, this study attempts to reveal the philosophical foundation employed in the textbook and its relation to curriculum 2013. This study was based on the inferential content analysis, so the object was an English textbook under the title â€˜Forward an English Course for Vocational School Students Grade Xâ€™. It applied linguistics and communication construct analysis to make an inference. Then, it recorded and categorized the data. The inferences were examined through attribution analysis. The results found there were ten points related to the content and the structure of the textbooks. It also revealed the philosophical foundations employed in the textbook, for instance, essentialism, perennialism, humanism, existentialism, social reconstruction, and progressivism.  These philosophical foundations are in line with the philosophical foundations implied in curriculum 2013. Finally, both English textbooks for vocational students and curriculum 2013 more concerned with the studentâ€™s character and skills. The skills that should be developed to engage with this 21st century such as critical thinking, problem-solving, communication, collaboration, creativity, and innovation.